Using GIS and SDSS Tools in the Design of a Photovoltaic System for a Built-up Roof - Davybida, Lidiia; Wyczałek, Ireneusz; Plichta, Artur (Geomatics and Environmental Engineering, 2022)
The design and installation of solar panels on the roofs of urban buildings often require consideration of the specific spatial conditions that affect their efficiency. The primary purpose of this work is to develop a procedure for designing and optimizing photovoltaic installations using geomatics methods and specific tools of GIS and CAD systems. The roof of the historic building A2, which is a part of the Poznań University of Technology campus, was selected as the tested object. Solar radiation modelling and determination of suitability zones were performed using SEBE (Solar Energy on Building Envelopes) in QGIS. Possible options for the placement of photovoltaic modules on the roof were simulated with CAD technique in the web-based HelioScope software. The results of the simulation show that the current roof area can generate electrical power of 99.9 MWh/year. The proposed methodology is universal for photovoltaic installations on built-up roofs and can be applied to other buildings and, consequently, the results obtained can be used to improve the content of the solar data urban geoportal.